The Neuroprotective Propensity of Organic Extracts of Acacia stenophylla Bark and Their Effectiveness Against Scopolamine-/Diazepam-Induced Amnesia in Mice - Shah D; Iqbal A; Alshehri FS; Ullah A; Ali G; Muhammad T; Ullah R; Sewell RDE; Althobaiti YS (Dove Medical Press, 2022)
Dawood Shah,1 Arshad Iqbal,1 Fahad S Alshehri,2 Aman Ullah,3 Gowhar Ali,4 Tahir Muhammad,5,6 Rahim Ullah,4,7 Robert D E Sewell,8 Yusuf S Althobaiti9,10 1Department of Botany, Islamia College Peshawar, Peshawar, Pakistan; 2Department of Pharmacology and Toxicology, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 3College of Pharmaceutical Sciences, Shifa Tameer-e-Millat University, Islamabad, Pakistan; 4Department of Pharmacy, University of Peshawar, Peshawar, Pakistan; 5Molecular Neuropsychiatry and Development (MiND) Lab, Campbell Family Mental Health Research Institute, Centre for Addiction and Mental Health, Toronto, ON, Canada; 6Institute of Medical Science, University of Toronto, Toronto, ON, Canada; 7Department of Pharmacy, Faculty of Life Sciences, Sarhad University of Science and Information Technology, Peshawar, Khyber Pakhtunkhwa, Pakistan; 8Cardiff School of Pharmacy and Pharmaceutical Sciences, Cardiff University, Cardiff, CF10 3NB, UK; 9Department of Pharmacology and Toxicology, College of Pharmacy, Taif University, Taif, Saudi Arabia; 10Addiction and Neuroscience Research Unit, Taif University, Taif, Saudi ArabiaCorrespondence: Gowhar Ali, Department of Pharmacy, University of Peshawar, Peshawar, 25120, Pakistan, Tel +92-919216750, Fax +92-91921813, Email gowhar_ali@uop.edu.pk; gohar.pharmacist@gmail.com Yusuf S Althobaiti, Department of Pharmacology and Toxicology, College of Pharmacy, Taif University, P.O. Box 11099, Taif, 21944, Saudi Arabia, Email ys.althobaiti@tu.edu.saBackground: Alzheimer's disease (AD) is a neurodegenerative disorder that is more prevalent in the elderly. There is extensive literature on using Acacia species against central nervous system disorders, although Acacia stenophylla has not been investigated for any neuroprotective potential. The purpose of the study was to elucidate the ameliorative effect of ethyl acetate (ASEE) and butanol (ASB) extracts from the bark of A. stenophylla on memory deficits and cognitive dysfunction in scopolamine- or diazepam-induced amnesia in mice.Methods: The phytochemical constituents of the extracts of A. stenophylla were determined by GC-MS and the in vitro anticholinesterase plus antioxidant activities were also evaluated. Anti-amnesic effects were determined employing the open field test, elevated plus maze (EPM), Morris water maze (MWM), and Y-maze paradigms.Results: The in vitro cholinesterase assays disclosed a concentration-dependent inhibition of both AChE and BuChE with IC50 values of 28.48 and 44.86 μg/mL for the ASEE extract and 32.04 and 50.26 μg/mL for the ASB extract against AChE and BuChE respectively. DPPH and H2O2 antioxidant assays revealed respective IC50 values for the ASEE extract of 28.04 and 59.84 μg/mL, plus 32.77 and 64.65 μg/mL for ASB extract. The findings revealed that both extracts possessed substantial antioxidant properties. Furthermore, these fractions restored scopolamine- and diazepam-induced memory deficits in a dose-dependent manner, as observed by a significant decrease in the transfer latency in EPM, reduction in escape latency, added time spent in the target quadrant in the MWM, and elevated spontaneous alternation behavior (SAB) in the Y-maze test.Conclusion: The ameliorative effect of A. stenophylla on scopolamine- and diazepam-induced amnesia can be attributed to antioxidant and anticholinesterase activity. Consequently, the use of A. stenophylla might be exploited in the alleviation of oxidative stress and the management of AD.Keywords: Acacia stenophylla, amnesia, oxidative stress, cognitive deficits, acetylcholinesterase